Ragam Genetik dan Heritabilitas Peubah Kualitatif dan Peubah Kuantitatif Dua Puluh Genotipe Cabai (Capsicum annuum L.) - Lasmiana, Lasmiana; Ganefianti, Dwi Wahyuni; Alnopri, Alnopri (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2016)
Chili development in Indonesia faces several constraints, mainly low yields and disease incidents. The improvement of chili traits through breeding programs requires information of genetic diversity, heritability, genetic advance and gene role. A study was conducted to assess the values of variability and heritability of qualitative and quantitative traits of 20 genotypes of chilli plants. The study was conducted in May-September 2015 on Experimental Field of Faculty of Agriculture, the University of Bengkulu. The 20 chili genotypes were arranged factorially in a Randomized Complete Block Design, with three replications. The results showed that the qualitative characters that have broad sense of variability and heritability were plant height, days to flower, time to harvest, fruit length, fruit diameter, fruit weight, and weight of fruit per plant, indicating that a selection can be done on those variables. Variability on qualitative characters was found on the position of the flower stalk (3 kinds), corolla color (4 kinds), color of corolla holder (3 kinds), corolla shapes (2 kinds), anther colors (4 kinds), pistil colors (3 kinds), colors of young fruit and ripe fruit (3 kinds), and fruit position (3 kinds).